Ashwathama Natyakavya in Creative Context - Yadav, Devsharan (Orchid Academia Siraha, 2022)
Critical contexts of lyrical poem ‘Ashwathama’ of lyricist Madhab Ghimire is presented in this article being full of poetic mood, the poet Ghimire has expressed the life consciousness and philosophical thinking of adulthood in this lyrical poem. Being full conscious, he has shown that the common place of people is alarming including injustice, tyranny, repression, exploitation, oppression, murder, violence, infanticide, feticide, abuse of power, degradation of human value in the world. It has expressed the need of peoples’ consciousness as the result of such criminal acts should be faced by people themselves and it aims to raise awareness of world and sufferings of people. Primary and secondary sources were used and library work, descriptive and analytical methods were used to analyse data. The main message of this poem is the sense of world brotherhood, brotherhood, mutual harmony, inspiration and ideology after the end of world war.